Owner Specific Factors, Firm Specific Factors, Internationalisation and Performance of SMEs in Sri Lanka: A Conceptual Framework (Journal of Business Management and Accounting, 2013)
As SMEs are internationalising at a faster rate today, theories that can explain SME internationalisation and performance are of extreme importance. At present there is no agreement among scholars on a single theoretical framework on SME internationalisation and performance. The literature suggested that contemporary firm performance is not associated with traditional factors. However, firm internationalisation and SME performance seem to be directly associated with unobservable owner and firm factors. However the literature indicated that past research does not conclusively prove the complex impact of owner or firm specific factors on SME internationalisation and performance. To fill this research gap, a conceptual framework that explains the relationship between internationalisation and performance was developed based on internationalisation, entrepreneurship, and organisational learning theories. Owner specific factors and firm specific factors in the conceptual framework are brand orientation, entrepreneurial orientation, and industry context respectively. In addition, this framework expands the scope of study in internationalisation-performance relationship by considering the moderating effect of organisational learning. Five hypotheses were developed to test the relationship between the variables in the conceptual framework. The outcome of this research can enhance the understanding of SME internationalisation process and provide some insights for policy makers, and SME owners and managers.